Blue light excitable Cu-based fluorescent material and preparation method thereof

By developing Complex 1 and Complex 2 of Cu-based fluorescent material, the problems of low photochemical stability and poor absorption band of copper halide cubic clusters in the prior art under ultraviolet irradiation conditions are solved, and efficient photoluminescence effect and good thermal stability are achieved under blue light excitation.

CN119552377AActive Publication Date: 2025-03-04CHANGZHOU UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411650773.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-03-04
Estimated Expiration
2044-11-19

AI Technical Summary

Technical Problem

In the prior art, copper halide cubic clusters have low photochemical stability under ultraviolet irradiation conditions, and their absorption bands in the visible region are poor, making them unsuitable for white LEDs excitation by blue light.

Method used

A blue-light-excited Cu-based fluorescent material was developed with a structure of complex 1 [CuBr(4-pytrz)2]n and complex 2 [Cu2I2(4-pytrz)]n. A high yield material was obtained by a simple preparation method, with a wide excitation band and good thermal stability.

Benefits of technology

The material can achieve quantum efficiency of 19.36% under blue light excitation, showing effective solid-state emission and enhanced light stability, with broad application prospects in white LEDs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention belongs to the field of photoelectric functional materials, and discloses a blue light excitable Cu-based fluorescent material and a preparation method thereof. The material is obtained by reaction of 4-pytrz and cuprous halide CuX (X = Br, I) at room temperature, and the 4-pytrz is 4-(4H-1, 2, 4-triazole-4-yl) pyridine. The invention designs and synthesizes two highly stable coordination polymers, namely a complex 1 [CuBr (4-pytrz) 2] n and a complex 2 [Cu2I2 (4-pytrz)] n, which have good thermal stability and both show wide excitation band coverage from a deep ultraviolet light region to a blue light region, the quantum efficiency can reach 19.36% under the excitation of blue light, and the complexes show effective solid emission and enhanced light stability and can be used for preparing a blue light emitting material. Wide application prospects are realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of optoelectronic functional materials, and in particular relates to a blue light-excitable Cu-based fluorescent material and a preparation method thereof. Background Art

[0002] Light-emitting diodes (LEDs) are attractive candidates for next-generation lighting and display applications due to their high efficiency, long operating lifetime, and high reliability. White correlated color temperature (CCT) with high color rendering index (CRI) can be obtained by exciting yellow phosphors using blue LED chips. Advanced commercial yellow LEDs are made from direct-bandgap III−V semiconductors, such as InGaN and AlGaInP, through expensive high-vacuum and high-temperature thin-film growth processes such as molecular beam epitaxy and metal−organic chemical vapor deposition. In an era of natural resource scarcity, high manufacturing costs limit their use in large-scale lighting and displays. Considering sustainable and environmentally friendly LED technology, it is highly desirable to develop inexpensive metal complexes as efficient yellow phosphors to replace rare-earth-based wLEDs.

[0003] In recent years, metal halide complexes have been widely studied as promising phosphors due to their broad excitation bands, tunable emission bands, and high brightness in the UV region. Cu(I) halide cubic clusters with the structural formula [Cu4X4L4] (X = Cl, Br, I; L = N or p-terminal ligand) exhibit excellent photoluminescence (PL) with high quantum yield. However, a major drawback of such complexes is their low photochemical stability under UV irradiation conditions. In addition, such complexes usually have poor absorption bands in the visible region and are not used in blue GaN LED chips. Broad excitation LEDs have several advantages, including high energy efficiency, long life, fast start-up, durability, small size, environmental protection, dimming capability, color selection, low heat generation, controllability, cost-effectiveness, and easy integration. Therefore, it remains a challenge to develop high-performance Cu(I)-based white LEDs with broadband excitation bands and superior thermal stability to meet the requirements of commercial applications. Summary of the invention

[0004] The purpose of the present invention is to provide a blue light excitable Cu-based fluorescent material and a preparation method thereof. The raw materials of the fluorescent material are easily available, the preparation method is simple, the yield is high, and the material has good thermal stability. The material exhibits a wide excitation band coverage from deep ultraviolet light to blue light regions. The material has a quantum efficiency of up to 19.36% under blue light excitation. The material is a highly efficient LED photoluminescent material with broad application prospects.

[0005] The above technical objectives of the present invention are achieved through the following technical solutions: The first aspect of the present invention provides a blue light-excitable inexpensive metal Cu-based fluorescent material, the structural molecular formula of which is: Complex 1 [CuBr(4-pytrz)2] n and complex 2 [Cu2I2(4-pytrz)] n ; wherein 4-pytrz is 4-(4H-1,2,4-triazol-4-yl)pyridine.

[0006] The complex 1 crystallized in the orthorhombic 'I ba m' space group with crystal parameters of a = 22.2556(2)Å, b = 12.92070(10)Å, c = 13.3239(2)Å, α = 90°, β = 90°, γ = 90°, Z = 4, V = 3831.39(7)Å 3 The asymmetric unit of complex 1 is composed of a crystallographically unique Cu(I) and two ligands 4-pytrz. The connections of 4-pytrz are disordered and have two connection modes, forming a two-dimensional (2D) MOF assembled by connecting CuBr and organic ligands 4-pytrz.

[0007] Complex 2 crystallized in the orthorhombic system 'P 21 21 2' space group with crystal parameters of a = 11.5513(12) Å, b = 14.4556(15) Å, c = 6.3291(7) Å, α = 90°, β = 90°, γ = 90°, Z = 4, V = 1056.84(19) Å 3 Complex 2 is characterized by Cu2I2 interconnected to form a single-stranded ladder ribbon extending along the crystallographic a-axis, and the 4-pytrZ segment connects [CuI] n ribbons, stacked along both sides of the copper iodide skeleton and extending along the crystallographic b-axis to form a two-dimensional plane, a two-dimensional (2D) MOF assembled by connecting Cu2I2 and 4-pytrz.

[0008] The second aspect of the present invention provides a method for preparing the above-mentioned blue light excitable inexpensive metal Cu-based fluorescent material, the method comprising: S1. Preparation of organic ligand 4-pytrz: Under the protection of inert gas, 4-aminopyridine and N,N'-bis(dimethylaminomethylene)hydrazine are placed in a flask, p-toluenesulfonic acid monohydrate and xylene are added, and the mixture is stirred, heated and refluxed for 23 to 24 hours. After the reaction is completed, the xylene is poured out, and the residue is washed with petroleum ether to remove the N,N-bis(dimethylaminomethylene)hydrazine therein. Dichloromethane is added to the remaining solid until it is just dissolved, and then the same volume of petroleum ether is added to recrystallize at low temperature to obtain a pure needle-shaped solid, which is the organic ligand 4-pytrz.

[0009] S2, preparation of complex: 4-pytrz and CuX (X = Br, I) are added to acetonitrile solvent, stirred thoroughly, filtered to remove precipitate, the filtrate is sealed with plastic wrap in a beaker and pierced, evaporated at room temperature for 1.5 to 3.5 days, filtered to obtain colorless transparent crystals, washed with solvent and distilled water, and dried to obtain pure yellow crystals. The preparation method has easy access to synthetic raw materials, simple synthesis method and high yield.

[0010] Furthermore, in the step S1, the molar ratio of the 4-aminopyridine, N,N'-bis(dimethylaminomethylene)hydrazine, and p-toluenesulfonic acid monohydrate is (74.4 ~ 75.1): (163.6 ~ 164.1): (7.0 ~ 7.21);.

[0011] Furthermore, in the step S1, the stirring heating reflux treatment time is 23 h to 24 h; the heating reflux temperature is 160° C. to 162° C.

[0012] Furthermore, in the step S2, the molar ratio of 4-pytrz to CuX is (0.09 ~ 0.11): (0.04 ~ 0.06); the volume of the acetonitrile solvent is 20 ml ~ 22 ml.

[0013] Furthermore, in the step S2, the standing volatilization is performed at a volatilization temperature of 15°C to 25°C.

[0014] The third aspect of the present invention provides the use of the above-mentioned blue light-excitable cheap metal Cu-based fluorescent material in a light emitting diode (LED).

[0015] The new blue light-excitable cheap Cu-based fluorescent materials synthesized by the present invention exhibit effective solid-state emission and enhanced light stability under blue light irradiation, with a blue light excitation wavelength range of 400 nm - 470 nm and a quantum efficiency of 19.36% under blue light excitation. The Cu-based fluorescent materials are promising blue light-excitable phosphors and have great application potential in full-spectrum white LEDs.

[0016] Compared with the prior art, the present invention has the following beneficial effects: (1) The wide excitation Cu(I)-based fluorescent materials provided by the present invention, both complexes 1 and 2, show wide excitation band coverage from deep ultraviolet light to blue light. The photoluminescence quantum yields (PLQY) of complexes 1 and 2 in the solid state are 5.76% and 19.36%, respectively.

[0017] (2) The organic ligand 4-pytrz provided by the present invention has a simple preparation method and can be connected and assembled with cheap CuX to obtain a two-dimensional (2D) Cu-based complex. The preparation method is simple and the yield is high.

[0018] (3) The quantum efficiency can reach 19.36% under blue light excitation. The complex exhibits effective solid-state emission and enhanced photostability, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the drawings in the embodiment are briefly introduced below.

[0020] Figure 1 The X-ray crystal structures of complexes 1 and 2; hydrogen atoms are omitted; Figure 2 is the infrared spectrum of the complex and the organic ligand 4-pytrz; Figure 3 is the powder X-ray diffraction pattern of complexes 1 and 2; Figure 4 Thermogravimetric diagrams of complexes 1 and 2; Figure 5 are the fluorescence excitation and emission spectra of complexes 1 and 2; Figure 6 is the photoluminescence quantum efficiency of complexes 1 and 2 measured at 298K; Figure 7 is the PL lifetime decay curve of complexes 1 and 2; Figure 8 Temperature-dependent photoluminescence spectra of complexes 1 and 2; Fig. 9 The temperature-dependent CIE diagrams of complexes 1 and 2. DETAILED DESCRIPTION

[0021] The following is a further description of a method for preparing a blue light-excitable inexpensive metal Cu-based fluorescent material and its technical effects proposed by the present invention. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.

[0022] In the following specific embodiments of the present invention, the method for preparing a cheap metal Cu-based fluorescent material that can be excited by blue light comprises the following steps: S1. Preparation of organic ligand 4-pytrz: Under the protection of inert gas, 4-aminopyridine (74.4 ~ 75.1mmol) and N, N'-bis (dimethylaminomethylene) hydrazine (163.6 ~ 164.1mmol) were placed in a flask, p-toluenesulfonic acid monohydrate (7.0 ~ 7.21mmol) and xylene (80 ~ 85 mL) were added, and heated to reflux at 160℃ ~ 162℃ for 23~24h. After the reaction, the xylene was poured out, and the residue was washed with petroleum ether to remove N, N-bis (dimethylaminomethylene) hydrazine, and the remaining solid was added with dichloromethane until it was just dissolved, and then the same volume of petroleum ether was added to recrystallize at a low temperature of 14~15℃ to obtain a pure needle-shaped solid, which is the organic ligand 4-pytrz.

[0023] S2. Preparation of complex: 4-pytrz (0.09 ~ 0.11 mmol) and CuX (X = Br, I) (0.04 ~ 0.06 mmol) were added to acetonitrile solvent (20 ~ 22 mL), stirred and filtered to remove precipitate, the mixed solution was sealed with plastic wrap in a beaker and pierced with holes, evaporated at room temperature for 3 days, filtered to obtain colorless transparent crystals, washed with solvent and distilled water, and dried to obtain pure yellow crystals.

[0024] The details of the reagents involved in the experiment are shown in Table 1; the reagents involved were used directly without further purification. The equipment and instruments used in the experiment are shown in Table 2.

[0025] Table 1 Reagents

[0026] Table 2 Main instruments

[0027] The present invention is described in detail below in conjunction with the embodiments, but they should not be construed as limiting the scope of protection of the present invention. Example 1

[0028] The present invention proposes a method for preparing a blue light-excitable cheap metal Cu-based fluorescent material, the method comprising a single crystal structure, the molecular formula of the single crystal structure of the complex material is: the structural molecular formula of the complex 1 is [CuBr(4-pytrz)2] n ; The structural formula of complex 2 is [Cu2I2(4-pytrz)] n ; Wherein, 4-pytrz is 4-(4H-1,2,4-triazol-4-yl)pyridine.

[0029] The specific preparation method is as follows: S1. Preparation of organic ligand 4-pytrz: Under the protection of inert gas, 4-aminopyridine (7.06 g, 74.4 mmol) and N,N'-bis(dimethylaminomethylene)hydrazine (23.23 g, 163.6 mmol) were placed in a flask, p-toluenesulfonic acid monohydrate (1.33 g, 7.0 mmol) and 80.0 mL of xylene were added, and the mixture was heated to reflux at 160°C for 24 h. After the reaction, the xylene was poured out, and the residue was washed with petroleum ether to remove N,N'-bis(dimethylaminomethylene)hydrazine. The remaining solid was added with dichloromethane until it was well dissolved, and then the same volume of petroleum ether was added to recrystallize at low temperature to obtain a pure needle-shaped solid, namely 4-(4H-1,2,4-triazol-4-yl)pyridine, with a yield of 64.72%.

[0030] S2. Preparation of complex 1: 4-pytrz (14.6 mg, 0.1 mmol) and CuBr (7.2 mg, 0.05 mmol) were added to 20 mL of acetonitrile solvent respectively, and the mixture was stirred and filtered to remove the precipitate. The mixed solution was sealed with plastic wrap and pierced in a beaker, and evaporated at room temperature for 3 days. Colorless transparent crystals were obtained by filtration, and washed with solvent and distilled water. Pure yellow crystals were obtained after drying with a yield of 48.96%.

[0031] S3. Preparation of complex 2: 4-pytrz (14.6 mg, 0.1 mmol) and CuI (9.5 mg, 0.05 mmol) were added to 20 mL of acetonitrile solvent respectively, and the mixture was stirred and filtered to remove the precipitate. The mixed solution was sealed with plastic wrap and pierced in a beaker, and evaporated at room temperature for 3 days. Colorless transparent crystals were obtained by filtration, and washed with solvent and distilled water. Pure yellow crystals were obtained after drying with a yield of 56.72%. Example 2

[0032] Crystals prepared by solvothermal method were collected under microscope, and crystallographic data of the complex were acquired on a Bruker APEX-II CCD instrument with graphene monochromatic radiation Mo. Kα (λ = 0.71073 Å) collected at the corresponding temperature. Data collection, data reduction and unit optimization were performed using two program packages, Bruker Instrument Service v4.2.2 and SAINT V8.34A. The structure of the complex was solved using the SHELXS program package, and the crystal data were optimized using the full matrix least squares method using the SHELXL program package. Absorption correction was performed using the multi-scan program package SADABS. The hydrogen atoms of the organic ligands were detected by riding mode in F 2The crystallographic data of the complex are shown in Table 3, and the partial bond length (Å) and bond angle (°) data of the complex are shown in Table 4.

[0033] Table 3 Crystallographic parameters of the complexes .

[0034] Table 4 Important bond lengths (Å) and bond angles (°) in the complex crystal structures Example 3

[0035] Infrared absorption spectroscopy analysis: Figure 2 As shown in the figure, the black line is the infrared absorption spectrum of the ligand 4-pytrz, and the red line is the infrared absorption spectrum of the complex. From this figure, it can be seen that the absorption spectrum of the complex and the absorption spectrum of the ligand can be very consistent, indicating that there is indeed an organic ligand in the complex. Example 4

[0036] Powder X-ray diffraction analysis: Figure 3 As shown, the black spectrum is the XRD pattern of the complex powder, and the red spectrum is the result obtained from the single crystal x-ray diffraction (SC-XRD) data. From the figure, it can be seen that the experimental value and the simulation value of the complex are in very good agreement, indicating that the complex is a pure phase. Example 5

[0037] Thermogravimetric analysis: Figure 4 As shown, the thermal stability of the complexes was studied by thermogravimetric analysis (TGA). From the TGA curves, it can be seen that the two complexes have high thermal stability and two-step decomposition. Due to the removal of halogen and part of the ligand, the first weight loss of complex 1 between 280°C and 500°C is about 21%~24%, and the first weight loss of complex 2 is about 31%~34%. The second weight loss between 500°C and 800°C can be attributed to the complete removal of the remaining ligands. Example 6

[0038] Fluorescence test: Figure 5 As shown, complexes 1 and 2 exhibit wide excitation band coverage from deep ultraviolet light to blue light. Under excitation at 470 nm, complex 1 exhibits a strong emission band centered at 615 nm, which is orange light emission with a half-maximum width (FWHM) of about 122 nm. Under excitation at 400 nm, complex 2 exhibits a strong emission band centered at 555 nm, which is yellow light emission with a half-maximum width (FWHM) of about 136 nm. Figure 6 As shown in Figure 2, the photoluminescence quantum yields (PLQY) of complexes 1 and 2 in the solid state are 5.76% and 19.36%, respectively. Figure 7 The photoluminescence (PL) decay curve is shown, which shows a double exponential decay. The PL lifetimes of complexes 1 and 2 are 1.26 µs and 2.47 µs, respectively. The solid-state photophysical data of the complexes at room temperature are shown in Table 5. The fluorescence decay rate of the complexes ( k r ) ( k r = Φ PL τ −1 ) are 4.57 × 10 4 s −1 and 7.48 × 10 4 s −1 Considering Φ PL = k r / ( k r + k nr ),in k nr is the rate of the nonradiative process including nonradiative singlet decay and ISC, k nr The estimated values ​​are 7.48 × 10 5 s −1 and 3.26 × 10 5 s −1 .

[0039] Table 5 Solid-state photophysical data of the complexes at room temperature

[0040] a Radiative rate constant calculated K r = Φ / τ. b Nonradiative rateconstant calculated K nr = (1-Φ) / τ. Example 7

[0041] Temperature-dependent photoluminescence spectroscopy analysis: Figure 8As shown in the temperature-dependent (TD) emission spectra, complexes 1 and 2 have similar luminescence temperature dependence, both exhibit thermal quenching effects, and the temperature-related emission changes of complexes 1 and 2 are slightly different. As the temperature gradually increases from 80 K to 500 K, the emission center of complex 1 shows a small blue shift of about 10 nm, and the emission center of complex 2 gradually increases from 80 K to 320 K, showing a 10 nm red shift, and then when the temperature increases to 500 K, it shows a 25 nm blue shift.

[0042] The change in CIE coordinates is consistent with the change in the maximum emission wavelength with temperature. Fig. 9 The corresponding CIE coordinates of complex 1 change from (0.6133, 0.3857) at 80 K to (0.5503, 0.4446) at 500 K. The corresponding CIE coordinates of complex 2 change from (0.4355, 0.535) at 80 K to (0.4407, 0.5201) at 320 K and finally to (0.3753, 0.5393) at 500 K.

[0043] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A blue light-excitable Cu-based fluorescent material, characterized in that: The blue light-excitable Cu-based fluorescent material is complex 1 or complex 2, and the structural molecular formula of complex 1 is: [CuBr(4-pytrz)2] n The structural formula of the complex 2 is: [Cu2I2(4-pytrz)] n , wherein 4-pytrz is 4-(4H-1,2,4-triazol-4-yl)pyridine, and n is an integer greater than or equal to 1.

2. The blue light excitable Cu-based fluorescent material according to claim 1, characterized in that: The unit cell parameters of the complex 1 are a = 22.2556(2) Å, b = 12.92070(10) Å, c = 13.3239(2) Å, α = 90°, β = 90°, γ = 90°, Z = 4, V = 3831.39(7) Å 3 ; The unit cell parameters of the complex 2 are a = 11.5513(12) Å, b =14.4556(15) Å, c = 6.3291(7) Å, α = 90°, β = 90°, γ = 90°, Z = 4, V = 1056.84(19)Å 3 .

3. The method for preparing a blue light excitable Cu-based fluorescent material according to claim 1 or 2, characterized in that: The steps include: S1. Preparation of organic ligand 4-pytrz: under the protection of inert gas, 4-aminopyridine and N,N'-bis(dimethylaminomethylene)hydrazine are added into a reactor, p-toluenesulfonic acid monohydrate and xylene are added, and the mixture is stirred, heated and refluxed for reaction. After the reaction is completed, the reaction product is collected, washed with petroleum ether, dissolved with dichloromethane, and then recrystallized by adding an equal volume of petroleum ether to obtain 4-(4H-1,2,4-triazol-4-yl)pyridine, abbreviated as 4-pytrz; S2. Preparation of complex: 4-pytrz and CuX (X = Br, I) are added to acetonitrile solvent respectively, stirred sufficiently, filtered, and the filtrate is sealed in a beaker with plastic wrap and pierced with holes, allowed to stand for volatilization, and the product is precipitated, filtered, washed, and dried to obtain the organic complex, wherein X = Br to synthesize complex 1, and X = I to synthesize complex 2.

4. The method for preparing a blue light excitable Cu-based fluorescent material according to claim 3, characterized in that: In the step S1, the molar ratio of 4-aminopyridine, N,N'-bis(dimethylaminomethylene)hydrazine, and p-toluenesulfonic acid monohydrate is (74.4-75.1): (163.6-164.1): (7.0-7.2).

5. The method for preparing a blue light excitable Cu-based fluorescent material according to claim 3, characterized in that: In the step S2, the molar ratio of 4-pytrz to CuX is (0.09 ~ 0.11): (0.04 ~ 0.06).

6. The method for preparing a blue light excitable Cu-based fluorescent material according to claim 3, characterized in that: In the step S1, the stirring, heating and reflux treatment is performed for 23 h to 24 h, and the reflux heating temperature is 160° C. to 162° C.

7. The method for preparing a blue light excitable Cu-based fluorescent material according to claim 3, characterized in that: In the step S2, the temperature of the standing volatilization is 15° C. to 25° C., and the standing volatilization time is 1.5 to 3.5 days.

8. Application of the blue light excitable Cu-based fluorescent material according to claim 1 or 2 in the field of light emitting diodes.

Citation Information

Patent Citations

  • 2-(1H-pyrazol-3-yl) pyridine copper complex as well as preparation method and application thereof

    CN103804398A

  • Methylpyridyl triazole copper [I] neutral complex luminescent materials and preparation method thereof

    CN105153225A

  • Method for preparing metal-organic framework material and application of metal-organic framework material

    CN117430823A

  • Light emitting CU (i) complexes

    US20100252820A1

  • TRIBOLUMINESCENT MATERIAL, USE OF A Cu COMPLEX AS A TRIBOLUMINESCENT MATERIAL, MECHANORESPONSIVE SENSOR AND METHOD FOR DETECTING A MECHANICAL LOADING

    WO2022014514A1